Digitalisation and neighbourhood cohesion in rural areas: Results of a mixed-method analysis - Kurtenbach, Sebastian; Küchler, Armin; Rees, Yann (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
This paper discusses digital neighbourhood communication in rural areas and its effects on local communal life. Therefore, survey data as well as guided interviews of residents in Metelen, county Steinfurt (Germany), are analysed. The results indicate that using digital neighbourhood platforms in rural communities intensifies contacts and further strengthens the feeling of social participation.However, digital neighbourhood contacts do not facilitate relationships concerning analogous material exchange, such as lending items. Furthermore, the analysis of the qualitative interviews shows that digital neighbourhood communication is used in the organisation of community life, presents local activities, and simplifies the organisation of local customs. All in all, those digital structures are mainly used for information purposes. Consequently, digital neighbourhood relations must be regarded when developing and organising future public services, although a functional usage is required to achieve a successful outcome. As digital contact emerges from analogous contact, occasions and infrastructure to actually ensure direct contact are inevitable.
Keywords: Digitalization; Neighbourhood relations; Rural areas; Social cohesion; Public services